Effects of melatonin treatment on the spermatogenesis and serum inflammatory cytokine levels in diabetic rats (Annals of Medical Research, 2021)
Aim: Diabetes mellitus (DM) is known to have side effects on sexual and reproductive functions in males. The aim of current study was to investigate the effect of melatonin treatment on spermatogenesis and serum inflammatory cytokine levels in diabetic rats. Material and Method: Eighteen adult Wistar albino male rats were divided randomly into three groups each containing 6 rats; control group (group 1), diabetic group (group 2), diabetic treated with melatonin group (group 3). Experimental diabetes was obtained by administrating 50 mg/kg streptozotocin. Melatonin treatment was administered intraperitoneally for 7 days at a dose of 20 mg, daily. Serum levels of interleukin-1 beta (IL-1β), interleukin 6 (IL-6) and tumor necrosis factor-alpha (TNF-α) were assayed. Spermatogenesis was evaluated according to Johnsen score at immunopathological examination.Results: The Johnsen scores in control, diabetic and treatment groups were 9.78, 8.91, and 9.61, respectively. Spermatogenesis was negatively affected in diabetic rats and significantly improved with melatonin therapy (p0.05). The serum levels of TNF-α in diabetic rats were observed to be increased compared to the control group (p0.05). The levels of serum IL-1β and TNF- α were significantly decreased with melatonin treatment. IL-6 levels were not different among the three groups (p=0.248). Conclusions: In the present study, intraperitoneal melatonin treatment was determined to have a positive effect of on spermatogenesis and caused a decrease in serum inflammatory cytokine levels in diabetic rats.Keywords: Cytokines; Diabetes Mellitus; Melatonin; Rats; Spermatogenesis.
Keywords: Cytokines; Diabetes Mellitus; Melatonin; Rats; Spermatogenesis.